Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1245/s10434-011-2073-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nodal Harvest in Colorectal Cancer: So What?

Abstract: Although improvements in the rate of adequate nodal harvest did occur over time, no corresponding meaningful improvement in clinical outcomes was noted. Given the need that quality indicators not only be associated with outcome, but also that outcome improves as such indicators are optimized, this study questions the inclusion of a nodal harvest≥12 lymph nodes as a quality indicator of colorectal cancer care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
2
11
1
Order By: Relevance
“…Higher yield was not associated with an increased number of metastatic nodes in the current study, which is in agreement with recent large cohorts (33,34). Each factor likely influences the LN sample to a modest, yet significant, degree, as demonstrated by the multivariable modeling in this series.…”
Section: Resultssupporting
confidence: 91%
“…Higher yield was not associated with an increased number of metastatic nodes in the current study, which is in agreement with recent large cohorts (33,34). Each factor likely influences the LN sample to a modest, yet significant, degree, as demonstrated by the multivariable modeling in this series.…”
Section: Resultssupporting
confidence: 91%
“…In other words, the poor lymph node harvest did not cause significantly lower metastasis discovery. Despite an improved lymph node harvest over time, Porter et al 35 could identify neither an increase in node positivity nor a change in outcome in population-based study. Recently, Parsons et al 36 also found in their SEER database study an clearly improved lymph node harvest over time but no increase in lymph node positivity.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have already reported an overall increase in LNY over the years without clinically relevant consequences, such as a rise in higher staged disease (i.e. N+) or improved outcomes [1,8,31,32]. Therefore, spending additional resources to find more small negative lymph nodes to reach this goal of 10 or 12 lymph nodes may in fact be some form of window dressing.…”
Section: Discussionmentioning
confidence: 99%
“…The number of lymph nodes needed for adequate staging of lymphatic spread of colorectal cancer continues to be a topic of debate [1]. Current guidelines advocate a minimum number of lymph nodes to be examined ranging from 10 in the Netherlands to 12 according to the American Joint Committee on Cancer Staging Manual [2].…”
Section: Introductionmentioning
confidence: 99%